1001 Algebra II Practice Problems For Dummies. - Sterling, Mary Jane (--For dummies., 2013)
Practice makes perfect-and helps deepen your understanding of algebra II 1001 Algebra II Practice Problems For Dummies takes you beyond the instruction and guidance offered in Algebra II For Dummies, giving you 1001 opportunities to practice solving problems from the major topics in algebra II. Plus, an online component provides you with a collection of chemistry problems presented in multiple choice format to further help you test your skills as you go. Gives you a chance to practice and reinforce the skills you learn in Algebra II classHelps you ref.